Markov-modulated Bernoulli-based performance analysis for BLUE algorithm under bursty and correlated traffics - Saaidah A.M.; Jali M.Z.; Marhusin M.F.; Abdel-Jaber H. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS/WOS